Effect of Accounts Receivable Turnover on Liquidity Level in Regional Drinking Water Company (PDAM) Tirta Silaupiasa, Asahan Regency - Anggi Mayasari Lubis; Rahmat Daim Harahap (Penerbit Jurnal Indonesia, 2022)
This research aims to analyze the influence of accounts receivable turnover on the level of liquidity in the Regional Drinking Water Company (PDAM) Tirta Silaupiasa, Asahan Regency. This research method uses quantitative methods. Data collection techniques used are observation and literature review. The data analysis technique used is linear regression analysis, product moment correlation and the coefficient of determination. Data analysis shows that the correlation coefficient of -0.716 which is the relationship between accounts receivable turnover and the level of liquidity in PDAM Tirta Silaupiasa Asahan Regency is strong. Receivable turnover has an effect on liquidity as much as 51.3%..